The Contribution of Bullying Involvement and Alexithymia to Somatic Complaints in Preadolescents - Valentina Levantini; Marina Camodeca; Nicolò Maria Iannello (MDPI AG, 2023)
Somatic complaints during preadolescence are connected to individual and contextual factors, and extant research highlights the relevance of alexithymia and bullying involvement. In this cross-sectional study, we explored the joint and unique influence of bullying involvement-as perpetrators, victims, or outsiders-and alexithymia on somatic complaints in a sample of 179 Italian middle-school students (aged 11-15). Findings revealed an indirect association between bullying perpetration and victimization complaints through alexithymia. We also found a significant direct association between victimization and somatic complaints. No significant association between outsider behavior and somatization was found. Our results revealed that bullying perpetration and victimization could increase youths' risk for somatic complaints and clarify one of the processes underlying this association. The current findings further emphasize the relevance of emotional awareness for youths' well-being and propose that implementing social-emotional skills might prevent some of the adverse consequences of being involved in bullying episodes.